Where angels fear to tread - Forster, E. M. (Edward Morgan), 1879-1970. (London : Hodder & Stoughton, 2010)
When a young English widow takes off on the grand tour and along the way marries a penniless Italian, her in-laws step in.
Adult.
Adult
Keywords: Culture conflict -- Fiction; Middle classes -- England -- Fiction; Culture conflict -- Fiction; Middle classes -- Fiction; England -- Fiction; Historical fiction; Humorous stories